HIPERREALITY OF SOCIAL MEDIA: A PHENOMENOLOGY STUDY OF SELF CONFESSION OF HOUSEWIVES OF FACEBOOK USERS - Damayanti, Nur Laili; Hidayat, Medhy Aginta (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
The phenomenon of hyperreality that is occurring in the community is increasingly apparent through social media, especially mothers in Rengel Village. Hyperreality is formed by the existence of social media for housewives to get self-recognition through Facebook. The purpose of this study was to analyze the self-recognition of housewives using Facebook in Rengel Village, Tuban Regency. The theory used is Jean Baudrillard'sHyperreality theory that hyperreality is a symptom of the emergence of various artificial realities that are more real than the original. The method used in this research is qualitative research with a phenomenological study approach. Subject selection techniques in this study using purposive samples, data sources from this study used primary data and secondary data. Data analysis using data reduction, data models, concluding. And check the validity of the data using source triangulation. The results showed housewives get self-recognition through various ways, namely, through photo uploads using a beautiful camera so that results look perfect than reality, through Facebook status that shows everyday life in order to get a response from other Facebook users, through photos daily activities so that other Facebook users know what is being done every day and get responses from other Facebook users, through photos that are marked there are various beauty products to be more interested in the products offered.